Chronic Pancreatitis with Hemosuccus Pancreaticus. The Diagnostic Contribution of Computed Tomography and Contrast Enhanced Ultrasonography – Case Report - Caraiani, C.; Chiorean, L.; Pascu, O.; Ciobanu, L.; Seicean, A.; Al Hajjar, N.; Zaharie, T.; Badea, R. (Zeitschrift für Gastroenterologie, 2014)
Hemosuccus pancreaticus is defined as upper gastrointestinal hemorrhage from the ampulla of Vater via the pancreatic duct. It is a rare disease, with non-specific presentation, challenging to diagnose and difficult to treat, with high mortality rates in untreated patients with massive bleeding. Given the intermittent nature of the bleeding, delays in diagnosis frequently occur. Timely diagnosis and treatment seem to result in markedly reduced mortality, therefore we emphasize the diagnostic contribution of imaging techniques by presenting the case of a patient with chronic pancreatitis in whom computed tomography established the diagnosis of blood in the Wirsung duct and contrast-enhanced ultrasound brought its added value by excluding the active bleeding.
Keywords: Haemosuccus pancreaticus; Computertomografie; gastrointestinale Blutung; Kontrastmittelsonografie; chronische Pankreatitis; Pankreasgang